Outcomes following multi-ligament knee reconstruction and novel meniscus radial repair technique: Return to Olympic level skiing - Berning, K. R.; DePhillipo, N. N.; Martin, B. M.; LaPrade, R. F. (Journal of Athletic Training, 2019)
Background: Multi-ligament knee injuries (MLKI) have a common occurrence during high-energy sports such as downhill ski racing. The occurrence of such injuries can be careerending and are often complicated with associated injuries such as complex, irreparable meniscus tears. Current literature reports on outcomes following these injuries for patients returning to normal activities of daily life but there is a lack of evidence reporting on return to high level sports. Furthermore, acute surgical treatment (< 3 weeks) has demonstrated superior outcomes compared to delayed treatment. Patient: 28-year-old female Olympic-level alpine skier sustained an acute right knee injury during a competitive skiing event. She described a noncontact mechanism at the time of injury which included deep knee fl exion with a varus force. She began to experience immediate anterolateral knee pain and swelling. Upon examination by the athletic trainer, there was effusion and swelling around the knee. Right knee extension was -7 degrees of hyperextension compared to -3 degrees of hyperextension on the left knee. Right knee fl exion was limited to 90 degrees due to swelling and pain. Ligamentous exam revealed a 3+ Lachman's test with a soft endpoint, 3+ pivot shift, and 3+ varus stress test at 30 degrees. The dial test was 1+ at 30 degrees of knee fl exion with rotation occurring from the anterolateral tibia. The proximal tibiofi bular joint had increased anteroposterior motion at 90 degrees of knee fl exion compared to the contralateral limb. An MRI demonstrated a complete tear of the ACL and attenuation of the LCL. The PCL, MCL, and popliteus tendon were intact. There was a possible tear noted in the posterior horn of the medial meniscus. The lateral meniscus displayed a complex radial tear near the root attachment. The popliteofi bular ligament appeared torn and there was increased swelling around the posterior ligamentous complex of the proximal tibiofi bular joint. Intervention or Treatment:Examination under anesthesia revealed complete grade III ACL and LCL tears. Prior to the surgery, bone marrow aspirate was harvested from the left posterior superior iliac crest and whole blood was drawn. Both were processed in a centrifuge to isolate bone marrow concentrate and plateletrich plasma, which were injected into the patient's knee at the end of the surgery for biological healing augmentation. Surgery was performed 4 days status post injury, which consisted of an open common peroneal nerve neurolysis, open LCL reconstruction with hamstring tendon autograft, open proximal tibiofi bular joint reconstruction with hamstring autograft, open popliteofi bular ligament repair, medial meniscus ramp repair, lateral meniscus twotunnel transtibial radial repair, and ACL reconstruction with patellar tendon autograft. Outcomes or Other Comparisons: Following surgery, the patient was non-weight bearing for 6 weeks with limited knee fl exion ROM to 90 degrees for 2 weeks. A return to snow progression was initiated at 7 months postoperatively. The athlete passed a functional sports test at 10 months postoperatively and was cleared to return to play with no restrictions. At 12 months postoperatively, the athlete placed in an Olympic qualifying ski race. At 14 months, the athlete competed in the 2018 Olympic Winter games and placed in the top 15 overall in super G and downhill events. Conclusions: Prompt diagnosis and surgical intervention are critical in the acute management of athletes with MLKI's. Anatomic surgical reconstruction provides the highest potential for any patient to return to activity following multi-ligament knee trauma. Clinical Bottom Line: This case highlights the ability of an athlete to return to elite level of competition following a multi-ligament knee injury in a safe, but timely manner. MLKI's should be treated within 3 weeks from injury to allow for optimal outcomes and return to preinjury level of sport.